Mediatinoscopy: about 50 cases - Pradines, Jorge C; Estefan Segui, Alberto (Cirugía del Uruguay, 1977)
In the period April 1971 - March 1976 the authors performed 50 mediastinoscopies in cases of multiple mediastino-pulmonary affections, 41 of which ( 82 % ) were positive and 9 ( 18 % ) negative. 47 patients showed clínica! or radioligical evidence of mediastine invasion and mediastinoscopy was positive in 87.9 % of cases. Out of· 24 broncogenic cancers, the procedure employed was directed towards etiological diagnosis (86.3 % positive) in 22 and in the remaining 2, towards establishing degree of extension of lesion. Mediastinoscopy made histological diagnosis possible in 7 out of 8 tumoral lymphopaties, 3 out of 5 tumors of mediastine and 2 out of 3 sarcoidosis. As supplementary procedure, it was employed in 2 esophageal cancers, 1 tracheal tumor and 1 aneurism of the innominate trunk. No serious complications appeared, nor any deatbs that could directly be connected with this procedure. Indications, limitations, complications and contraindications are discussed. On the basis of results obtained, experience acquired in the employment of suprasternal mediastinoscopy and review of literature on the subject.